2021
DOI: 10.1371/journal.pone.0249915
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and ecological risk assessment of 4,4’-dihydroxybenzophenone, 2,4,4’-trihydroxybenzophenone and 4-MBC in ultraviolet (UV)-filters

Abstract: Ultraviolet (UV) filters are used in cosmetics, personal care products and packaging materials to provide sun protection for human skin and other substances. Little is known about these substances, but they continue to be released into the environment. The acute toxicity of 4,4’-dihydroxybenzophenone, 2,4,4’-trihydroxybenzophenone and 4-MBC to Chlorella vulgaris and Daphnia magna were analyzed in this study. The 96 h-EC50 values of 4,4’-dihydroxybenzophenone, 2,4,4’-trihydroxybenzophenone and 4-MBC on C. vulga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Other tests with organisms from higher trophic levels confirmed the possibility of antagonistic interaction between toxic compounds in mixtures. Antagonistic interaction of binary and ternary mixtures of 4,4′-dihydroxybenzophenone (4,4′-HBP), 2,4,4′-trihydroxybenzophenone (2,4,4′-HBP), and 4-MBC that triggered toxicity against Chlorella vulgaris was observed by Han et al [ 103 ]. Du et al [ 102 ] have shown that the toxic effects of the mixture composed of BP-3 and benzophenone-4 against Chlorella vulgaris , Daphnia magna , and Danio rerio were also antagonistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other tests with organisms from higher trophic levels confirmed the possibility of antagonistic interaction between toxic compounds in mixtures. Antagonistic interaction of binary and ternary mixtures of 4,4′-dihydroxybenzophenone (4,4′-HBP), 2,4,4′-trihydroxybenzophenone (2,4,4′-HBP), and 4-MBC that triggered toxicity against Chlorella vulgaris was observed by Han et al [ 103 ]. Du et al [ 102 ] have shown that the toxic effects of the mixture composed of BP-3 and benzophenone-4 against Chlorella vulgaris , Daphnia magna , and Danio rerio were also antagonistic.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other data suggest that the interactions between UV filters in mixtures could lead to additive or synergic endpoints. In the study referenced above one combination of a binary mixture composed of 4,4′-HBP and 4-MBC exhibited an additive toxic effect [ 103 ]. Cahova et al [ 47 ] indicated higher toxicity after the exposition of Danio reiro embryos to a mixture of 4-MBC and OCR, a mixture of BP-3, EHMC, and 2-phenylbenzimidazole-5-sulfonic acid (PBSA) and the combination of all five UV filters than in case of exposition to a single solution.…”
Section: Discussionmentioning
confidence: 99%
“…Some very useful model organisms within the 4-MBC research are molluscs (Mytilidae), American bullfrog (Lithobates catesbeianus), copepod (Tigriopus japonicus) and the freshwater caddisfly (Sericostoma vittatum). [46][47][48] Some other organisms involved in studying 4-MBC's effects are Japanese medaka (Oryzias latipes), Harlequin fly (C. riparius), zebrafish (Danio rerio), Senegalese sole (Solea Senegalensis) and Iberian green frog (Pelophylax perezi). The downside of many of these organisms, such as Japanese medaka and Harlequin fly, is that they are sensitive fish useful for ecotoxicity tests but less useful for studying 4-MBC's effects directly on human health.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the mammalian models, fish and aquatic animals are good model organisms to study how 4‐MBC affects embryogenesis, as the fish embryos lack the protective placenta and are easy to study in terms of progression. Some very useful model organisms within the 4‐MBC research are molluscs ( Mytilidae ), American bullfrog ( Lithobates catesbeianus ), copepod ( Tigriopus japonicus ) and the freshwater caddisfly ( Sericostoma vittatum ) 46–48 . Some other organisms involved in studying 4‐MBC's effects are Japanese medaka ( Oryzias latipes ), Harlequin fly ( C. riparius ), zebrafish ( Danio rerio ), Senegalese sole ( Solea Senegalensis ) and Iberian green frog ( Pelophylax perezi ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation